(untitled) (Italian Journal of Public Health, 2009)
Background: The aetiology of multiple sclerosis (MS) is unclear, but numerous studies suggest that different exogenous factors can lead to the development of the disease in genetically susceptible individuals. The objective of this case-control study was to determine the role of food and dietary patterns in patients with MS in the population of Belgrade (Serbia). Methods: In this matched case-control study, we included 110 cases with definite MS according to McDonald’s criteria, in whom the onset symptoms occurred up to 2 years prior to the interview, who were followed-up at the Institute of Neurology, Clinical Centre of Serbia, Belgrade. The identical number of controls from the same institution, individually matched by sex, age and area of residence, was recruited from patients with various non-autoimmune neurological disorders. Dietary information was obtained by using a frequency history approach. Results: According to univariate conditional logistic regression analysis the following factors were significantly related to MS: body mass index (BMI) less than 25 (OR=2.2, p=0.009), frequent consumption of beef (OR=1.7, p=0.043), chicken (OR=2.0, p=0.045), meat of the lamb (OR=2.1, p=0.013), butter (OR=1.7, p=0.056) and ice-cream (OR=1.8, p=0.031), with dose-response relationship. Consumption of majority of various fruit was more frequently reported by controls. According to multivariate conditional logistic regression analysis, BMI less than 25 (OR=2.3, p=0.008), consumption (weekly) of beef (OR=2.0, p=0.017) and butter (OR=1.9, p=0.027) was significantly related to MS, while regular consumption of cherry (OR=0.4, p=0.024) had protective role. Conclusions: This study might assist in potential defining of the dietary factors that could contribute to the risk of developing MS